Bach1 gene ablation reduces steatohepatitis in mouse MCD diet model - Inoue, Motoki (the Society for Free Radical Research Japan, 2011)
Bach1 is a transcriptional repressor of heme oxygenase-1 (HO-1, a.k.a. HSP-32), which is an inducible enzyme and has anti-oxidation/anti-inflammatory properties shown in various models of organ injuries. Since oxidative stress plays a pivotal role in the pathogenesis of nonalcoholic steatohepatitis (NASH), HO-1 induction would be expected to prevent the development of NASH. In this study, we investigated the influence of Bach1 ablation in mice on the progression of NASH in methionine-choline deficient (MCD) diet model. Bach1 ablation resulted in significant induction of HO-1 mRNA and its activity in the liver. When fed MCD diet, Bach1(−/−) mice exhibited negligible hepatic steatosis compared to pronounced steatohepatitis in wild type mice with 6-fold increase in hepatic triglyceride content. Whereas feeding of MCD diet decreased mRNA expressions of peroxisome proliferator-activated receptor (PPAR) α and microsomal triglyceride transfer protein (MTP) in wild type mice, there were no change in Bach1(−/−) mice. In addition, hepatic concentration of malondialdehyde (MDA), a biomarker for oxidative stress as well as plasma alanine aminotransferase (ALT) was significantly lower in Bach1(−/−) mice. These findings suggest that Bach1 ablation exerts hepatoprotective effect against steatohepatitis presumably via HO-1 induction and may be a potential therapeutic target.